(untitled) (Research, Society and Development, 2019)
The population growth fostered several segments of industry, in which one finds among them the construction industry can. In this sense of growth, the construction of houses passed and be considered a fundamental part of the economy of the country, by employing a large amount of manpower besides fomenting a whole chain of suppliers. To boost the construction, the reinforced concrete had a primordial role because with its use it was possible to optimize time and resources, obtaining safer constructions and of better quality. The objective of this work is to demonstrate the use of reinforced concrete in the structural systems of buildings, observing the different normative criteria in relation to the understanding of the design and dimensioning of the structures. The paper describes the history of reinforced concrete in civil construction, exposing its evolution that was provided by the technical diffusion of the methods of calculations; presents the reinforced concrete and its components, the structural elements of the reinforcing concrete, the technical procedures for the use of this constructive system. In demonstrating the general aspects of the reinforced concrete and the technical procedures for its use, it is intended to contribute to projects being better observed in their elaboration, so that the specifications and procedures are followed during the execution.